THE ROLE OF EXPERIENTAL MARKETING IN THE PURCHASE DECISION OF THE BODY SHOP COSMETIC PRODUCTS IN JEMBER REGENCY - Andarini, Syarifah Fidelia; Suharto, Akhmad; Rusdiyanto, Rusdiyanto (Univesitas Muhammadiyah Tangerang, 2025)
The cosmetics industry is an industry that can be said to have good growth and development in Indonesia. People, especially women, are increasingly aware of the importance of using cosmetics daily. This study aims to test the influence of Experiential Marketing variables on purchasing decisions, and purchasing decision variables on experiential marketing variables. The type of research conducted is quantitative. The object of this study is the cosmetic product of the body shop Lippo Plaza Jember. The sampling technique was 100 respondents. The data collection method was by distributing questionnaires to respondents who had purchased the cosmetic product of the body shop Lippo Plaza at least 1 time. This study uses descriptive and path data analysis. The results of this study indicate that the Experiential Marketing variables sense, feel, think, act, and relate significantly influence customer decision variables.